#TITLE_ALTERNATIVE# - RAMDANI (NIM: 25111006); pembimbing: Dr. Ir. Kosasih Priyatna MSc.; Dr. Heri Andreas ST. MT., DADAN
Reference frame is a practical realization of a reference system, and the reference system is a system used in the definition of a coordinate. Height reference system is realized by a vertical frame shaped Vertical Control Network (JKV). There are several JKV in Jakarta including NWP, PP and TTG, where the last two JKV PP and TTG are often used. PP is only applicable to Jakarta (local) while TTG is for national use. Natural changes that occurred in Jakarta, especially the land subsidance, which has a mean about 3,5 cm/year as well as sea level rise of about 8 mm/year, will affect the height system as well as the reference system, so the JKV is no longer up to date. In addition to these changes the selection of high datum will affect the JKV. This study will evaluate the vertical refference frame in Jakarta under those circumstances in order for the future JKV as wel as its referenced that can accommodate the changes that occur both on land and at sea. The use of high reference (high datum) geoid in Jakarta will be better because of this geoid will be slightly affected by these changes. The GIF48 which has a standard deviation of the difference geoid height with GNSS-Leveling at 0,162 m and it is better than EGM2008 with 0.172 m is suitable for use in the calculation of the geoid height. Geoid through a mean high higher water coupled with the safety factor to anticipate the sea level rise can be used for high datum as this will ensure that the water flows into the sea in a specified period. The use of the semi-dynamic JKV would be better to apply in Jakarta due to the semi-dynamic JKV will be able to accommodate the changes.